Étudier la socialisation langagière des étudiant·e·s internationaux·ales par des ateliers cartographiques - Félix Danos; Jean François Grassin (Recherches en didactique des langues et des cultures)
We propose a reflection on the question of the urban and daily mobility of international students (IS) and seek to understand how spatial practice contributes to language socialization and cultural repertoires, acquired as students inhabit the city. We draw on cartographic workshops (1) as heterogeneous spaces where students are led to narrate their socializing experiences in the urban territory in which they live, and (2) as a locus of socialization. Through the discursive analysis of several small stories of experience, we show that these workshops can provide a form of support for certain modes of navigation in the urban territory, which are conducive to learning.